The Influence of Organizational Culture on Teacher Commitment and Performance at Madrasah Aliyah Ma'arif NU 5 Sekampung - Siti Mutmainah; Muhammad Yusuf; Eka Fitria Ningsih (CV. Bimbingan Belajar Assyfa, 2025)
This study aims to analyze the influence of organizational culture on teacher commitment and performance at Madrasah Aliyah Ma'arif NU 5 Sekampung. A strong and conducive organizational culture is believed to be an important factor in increasing teachers' commitment to the institution and encouraging optimal performance. This study employs a quantitative approach with a survey method. The research population consisted of all 42 teachers at Madrasah Aliyah Ma'arif NU 5 Sekampung, with a saturated sample of 42 respondents. Data collection was conducted using a questionnaire with a Likert scale of 1-5 that had been tested for validity and reliability. Data analysis used descriptive statistics and multiple linear regression analysis with SPSS software. The results showed that: (1) organizational culture has a positive and significant effect on teacher commitment; (2) organizational culture has a positive and significant effect on teacher performance; (3) teacher commitment has a positive and significant effect on teacher performance; and (4) teacher commitment mediates the influence of organizational culture on teacher performance. These findings indicate that a strong organizational culture, which includes shared values, norms, and positive work ethic, can increase teachers' affective, normative, and continuance commitment, which in turn encourages improvement in their performance. This research contributes to the development of Islamic education management in madrasahs, particularly in understanding the mechanism of organizational culture's influence on teacher performance through commitment as a mediating variable